KOMPETENSI GURU PAI IDEAL DITINJAU DARI SOSOK NABI MUHAMMAD SAW SEBAGAI PENDIDIK - Nurullita Al Munawaroh; Aprilia Putri Hapsari; Nisa Amalia Kholifah (Intelegensia : Jurnal Pendidikan Islam, 2022)
AbstractConsidering the importance of the role of teachers, especially PAI teachers, in the mission of moral reconstruction of the nation's generation, the researchers are interested in conducting research on the topic of the personality of PAI teachers. Talking about the personality of PAI teachers, we usually review the figure of the Prophet Muhammad. as a role model for all mankind. He is an example not only in daily behavior, but also in the context of educating. This research was conducted with the aim of providing an overview of how a PAI teacher is able to carry out his duties through several basic competencies that have been formulated nationally and also through a study of the professional values of educators in terms of the figure of the Prophet Muhammad. The methodology used is a qualitative approach with a literature study and the research results are presented descriptively. The results of this study show how important it is to master the basic competencies of PAI teachers and the virtue of imitating the competencies of educators that have been interpreted from the figure of the Prophet Muhammad. As educators, apart from the need to master basic competencies, it is also important for us to understand and apply appropriate strategies and methods in educating students and leading the running of moral education based on Islamic values in the community. Keyword: personality; competencies of PAI’s teacher; Propeth Muhammad.AbstrakMeninjau betapa pentingnya peran guru khususnya guru PAI, dalam misi rekonstruksi moral generasi bangsa, maka peneliti tertarik untuk melakukan penelitian dengan topik kepribadian guru PAI. Berbicara tentang kepribadian guru PAI, lazimnya kita menelaah kembali sosok Rasulullah Muhammad saw. sebagai panutan seluruh umat manusia. Beliau merupakan tauladan bukan hanya pada perilaku sehari-hari, namun juga dalam konteks mendidik. Penelitian ini dilakukan dengan tujuan memberi gambaran bagaimana seorang guru PAI mampu melaksanakan tugasnya melalui beberapa kompetensi dasar yang telah dirumuskan secara nasional dan juga melalui telaah nilai-nilai professional pendidik ditinjau dari sosok Rasulullah saw. Adapun metodologi yang diguakan adalah pendekatan kualitatif dengan studi literature dan hasil penelitian dipaparkan secara deskriptif. Hasil pada penelitian ini menunjukkan betapa pentingnya penguasaan kompetensi dasar guru PAI dan keutamaan dari meneladani kompetensi pendidik yang telah diinterpretasikan dari sosok Nabi Muhammad saw. sebagai pendidik selain perlu menguasai kompetensi dasar, juga penting bagi kita untuk memahami sekaligus menerapkan strategi dan metode yang tepat dalam mendidik peserta didik maupun memimpin berjalannya pendidikan moral berbasis nilai-nilai keislaman di lingkup masyarakat.Kata kunci: kepribadia;  kompetensi guru PAI;  Nabi Muhammad.